THE PROBLEM OF CREATION OF INFORMATION AND COMMUNICATION MEDIUM AS A MEANS OF TRAINING TEACHERS OF PHYSICS - A. Ivanitsky (Kherson State University, 2012)
The article considers the problem of creation of information and communication medium as a means of training teachers of physics based three-component system of networked information and communication systems